2023
DOI: 10.1037/trm0000398
|View full text |Cite
|
Sign up to set email alerts
|

The curvilinear relationships between posttraumatic growth and posttraumatic stress, depression, and anxiety.

Abstract: The literature suggests that the relationship between posttraumatic growth (PTG) and posttraumatic stress (PTS) is curvilinear, and that type or severity of trauma may affect this relationship. The relationship between depression, anxiety, and PTG is understudied. Participants (N = 541) were emerging adult students at a southeastern United States university who had been exposed to one or more posttraumatic stress disorder diagnostic Criterion A events. Participants completed a cross-sectional survey with self-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 71 publications
0
4
0
1
Order By: Relevance
“…The majority identified as women, as White/European American, and as freshmen or first-year university students. Over half of the respondents had been exposed to one or more potentially traumatic events, as reported in a previous study with this sample (Weber & Schulenberg, 2022).…”
Section: Methodsmentioning
confidence: 58%
“…The majority identified as women, as White/European American, and as freshmen or first-year university students. Over half of the respondents had been exposed to one or more potentially traumatic events, as reported in a previous study with this sample (Weber & Schulenberg, 2022).…”
Section: Methodsmentioning
confidence: 58%
“…Another important issue is that, yet to date, there has been no consensus about the relationship between experiencing distress and positive posttrauma changes. A review of the current studies found a diverse trend in the relationship between distress symptoms and PTG, such as an inverted-U curvilinear (Weber & Schulenberg, 2023), a linear positive relationship between (Maia et al, 2022), or a linear negative relationship (Thomas et al, 2021). This study will further examine the relationship between fear of COVID-19 and PTG, and we propose the following hypothesis:…”
Section: Fear Of Covid-19 and Ptgmentioning
confidence: 83%
“…Так в одному із сучасних психологічних досліджень підкреслюється оберненопропорційний зв'язок між показниками посттравматичного стресу та посттравматичного зростання, а саме підтверджується, що відсутність клінічно значущої депресивної та тривожної симптоматики є ознакою більшості випадків посттравматичного зростання. Зокрема наголошується, що відновлення від посттравматичного стресу через створення нових життєвих сенсів призводить до посттравматичного зростання (Weber & Schulenberg, 2022).…”
Section: концептуальні підходи до розуміння феномену посттравматичног...unclassified